2023
DOI: 10.3390/foods12183385
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-Based Microfluidics as a Platform to Design Food-Grade Delivery Systems Based on the Entrapped Compound Type

Jhonatan Rafael de Oliveira Bianchi,
Lucimara Gaziola de la Torre,
Ana Leticia Rodrigues Costa

Abstract: Microfluidic technology has emerged as a powerful tool for several applications, including chemistry, physics, biology, and engineering. Due to the laminar regime, droplet-based microfluidics enable the development of diverse delivery systems based on food-grade emulsions, such as multiple emulsions, microgels, microcapsules, solid lipid microparticles, and giant liposomes. Additionally, by precisely manipulating fluids on the low-energy-demand micrometer scale, it becomes possible to control the size, shape, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…The TFP offers flexibility with tubes of varying diameters, increasing the range of possible droplet diameters and volumes that can be achieved [28]. The TFP is faster to produce and easily adaptable, as no new constructions are needed for droplet volume adaptation, as described in flow-focusing solutions using chips [47,48]. The TFP-based droplet generation, as depicted in Figure 3, aligns with numerical studies on chip-based droplet generators, where the droplet volume increases with decreasing flow rate ratios from the continuous to the disperse phase ( .…”
Section: Discussionmentioning
confidence: 99%
“…The TFP offers flexibility with tubes of varying diameters, increasing the range of possible droplet diameters and volumes that can be achieved [28]. The TFP is faster to produce and easily adaptable, as no new constructions are needed for droplet volume adaptation, as described in flow-focusing solutions using chips [47,48]. The TFP-based droplet generation, as depicted in Figure 3, aligns with numerical studies on chip-based droplet generators, where the droplet volume increases with decreasing flow rate ratios from the continuous to the disperse phase ( .…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of nanotechnology, microfluidic technology, as a precision and efficient micro and nano scale processing method, has shown unique advantages in the design and preparation of nanomaterials [ 1 , 2 , 3 , 4 ]. By precisely manipulating the fluid flow, mixing and reaction conditions in microfluidic channels at the micron to nanometer level, microfluidic technology achieves a high degree of control over the morphology, size, surface properties and other microscopic characteristics of nanoparticles, which greatly promotes the wide application of functional nanoparticles in biomedicine, catalysis, sensing and environmental remediation [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that using the microfluidic system, researchers can precisely control the mixing process of zein ethanol soluble solution with anti-solvent or other additives and effectively prepare zein nanoparticles with uniform particle size and good stability through rapid diffusion and solidification at the micro scale [ 8 ]. Against this background, microfluidic technology provides a new strategy to solve the above problems.…”
Section: Introductionmentioning
confidence: 99%